Palm Oil Mill Effluent as an Environmental Pollutant : Indonesia Palm Oil Industry - Najwa Maulida; Dian Saputri; Joseph Natanael; Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2023)
Indonesia is one of the countries with the world's greatest processed palm oil reserves and production. The waste product of palm oil manufacturing is known as POME (palm oil mill effluent). POME can be used as a source of electricity and biogas, as well as a potential renewable energy source.